Wound healing activity of curcumin conjugated to hyaluronic acid: in vitro and in vivo evaluation. (4th July 2018) - Sharma, Mrinalini; Sahu, Khageswar; Singh, Surya Prakash; Jain, Beena
Abstract: Curcumin is a promising wound healing agent but its clinical application is limited due to hydrophobicity and lack of stability. In this article, we report the results of a study on wound healing efficacy of curcumin conjugated to hyaluronic acid (HA) which is a natural polysaccharide known to influence the healing process. Studies on proliferation, antioxidant activity and scratch wound healing carried out in human keratinocyte cells revealed that HA-conjugated curcumin treatment enhanced cell proliferation, decreased oxidative damage induced by H2 O2 and also improved migration of cells in scratch wounds as compared to treatment with native curcumin. HA conjugated curcumin exhibited bactericidal activity in dark and phototoxicity when irradiated with blue light against antibiotic resistant bacteria. Furthermore, wound healing efficacy studied in diabetic mice demonstrated that topical application of the conjugate on wounds led to better healing as compared to treatment with HA-free curcumin and HA alone. These results suggest that HA conjugation is a promising formulation of curcumin for enhancing its healing efficacy.